Audit Sistem Informasi Aplikasi Gramedia Digital menggunakan framework COBIT 5 - Nila Ilma Atqiyak; Dwi Budi Santoso (STEKOM PRESS, 2022)
Gramedia Digital application itself is a good innovation in the digital era now. Even though it has been used by users but there are still some obstacles or lack of information contained on the application, therefore it requires maturity and capability assessment of the application. The COBIT 5 framework is an IT audit standard that has been issued by ISACA, COBIT 5 itself has a total of 11 domains but this time the research only focuses on 5 domains namely EDM05, APO05, BAI04, DSS01, MEA01. The results of the maturity and capability level calculations from Gramedia Digital applications resulted in an average of EDM05 with a result of 2.7, APO05 with a result of 2.8, BAI04 with a result of 2.7, DSS01 with a result of 2.7, MEA01 with a result of 2.8. And the average capability generated by these domains is rounded to 3. The conclusion in this study gramedia Digital application has not met the targeted target of 4.